Implementation of Risk Management as an Anti-Fraud Strategy at PT BRI Sudirman Branch, Pekanbaru - Khoirunnisa, Khoirunnisa; Aristi, Mentari Dwi (Research in Accounting Journal (RAJ), 2023)
Consistent application of Risk Management in every business and operational activity can make the company a healthy company and grow sustainably. The implementation of good risk management is also able to minimize and prevent fraud. In December 2019, the Financial Services Authority issued guidelines on “Application of Anti-Fraud Strategy for Commercial Banks” which states that the implementation of anti-fraud strategy is part of the implementation of risk management, particularly those related to aspects of the internal control system. This study aims to determine whether the implementation of risk management by PT BRI KC Pekanbaru Sudirman is in accordance with OJK Regulation No. 13/POJK.03/2016 and POJK No. 39/POJK.03/2019. The method used in this research is a qualitative method, data collection techniques are carried out by conducting interviews and observations for some time. The results of this study are the implementation of risk management against anti-fraud strategies at PT BRI KC Pekanbaru Sudirman in accordance with OJK regulations no. 18/POJK.03/2016 concerning the implementation of risk management for commercial banks and POJK No. 39/POJK.03/2019 regarding guidelines for implementing anti-fraud strategies for commercial banks. The implementation of good risk management that has been carried out at PT BRI KC Pekanbaru Sudirman has reduced the rate of fraud